Stock Market Reaction to Corporate Announcements on the NSE and the Efficient Market Hypothesis - Ibrahim, Filsan Sidow (2007)
This paper examines the efficiency of the Nairobi Stock Exchange which is Kenya’s only stock exchange market. The operation and efficiency of the Nairobi Stock exchange has been of considerable research interest of late. Several researchers have studied about NSE‘s pricing efficiency from 1980 to 1990. This dissertation broadens the debate by further testing the semi-strong form of stock market efficiency in Kenya. The paper investigates whether investors in Kenya can predict and create profitable trading strategies based on the announcement of yearly company earnings reports.The literature review of this dissertation contains a review of the theory of Efficient Market Hypothesis (EMH), researches about capital markets and market efficiency, other emerged theories after EMH such as behavioral finance, and event studies. The date of this research is from 2002 to 2006. An event study approach is employed in order to investigate the share price reaction around the yearly company earnings announcement, and the market model is used to predict expected stock returns. We find that there is no significant relationship between stock returns and corporate announcement. The results of the abnormal residual returns showed inconsistent which could be attributed to normal trading activities of the NSE. Though, the finding of this dissertation shows that the NSE is not efficient in the semi strong form of the EMH. The results are subject to the limitations highlighted in the study. The inefficiency of the NSE can be attributed to factors such as lack of demand and supply for securities, market infrastructure, low listed companies, and lack of ways of attracting small investors since majority stock traders are institutional investors.